2018 25th Asia-Pacific Software Engineering Conference (APSEC) 2018
DOI: 10.1109/apsec.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Power-Aware Allocation of Fault-Tolerant Multirate AUTOSAR Applications

Abstract: Software-to-hardware allocation plays an important role in the development of resource-constrained automotive embedded systems that are required to meet timing, reliability and power requirements. This paper proposes an Integer Linear Programming optimization approach for the allocation of faulttolerant embedded software applications that are developed using the AUTOSAR standard. The allocation takes into account the timing and reliability requirements of the multirate software applications and the heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Random generated mixed-critical runnable sets have been used for the performance evaluation, which later demonstrated that the presented approach can drastically reduce the memory stack usage of the system. Targeting the same systems that comply with the AUTOSAR standard, Nesredin Mahmud et al [ 24 ] aim to optimize the allocation of fault tolerant embedded software applications. The presented optimization is based on an Integer Linear Programming model that minimizes the total power consumption of the system while taking into consideration the imposed timing and reliability requirements.…”
Section: Previous Workmentioning
confidence: 99%
“…Random generated mixed-critical runnable sets have been used for the performance evaluation, which later demonstrated that the presented approach can drastically reduce the memory stack usage of the system. Targeting the same systems that comply with the AUTOSAR standard, Nesredin Mahmud et al [ 24 ] aim to optimize the allocation of fault tolerant embedded software applications. The presented optimization is based on an Integer Linear Programming model that minimizes the total power consumption of the system while taking into consideration the imposed timing and reliability requirements.…”
Section: Previous Workmentioning
confidence: 99%